2011
DOI: 10.1101/gr.121541.111
|View full text |Cite
|
Sign up to set email alerts
|

Open chromatin defined by DNaseI and FAIRE identifies regulatory elements that shape cell-type identity

Abstract: The human body contains thousands of unique cell types, each with specialized functions. Cell identity is governed in large part by gene transcription programs, which are determined by regulatory elements encoded in DNA. To identify regulatory elements active in seven cell lines representative of diverse human cell types, we used DNase-seq and FAIRE-seq (Formaldehyde Assisted Isolation of Regulatory Elements) to map ''open chromatin.'' Over 870,000 DNaseI or FAIRE sites, which correspond tightly to nucleosome-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

33
464
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 467 publications
(499 citation statements)
references
References 64 publications
33
464
1
1
Order By: Relevance
“…2d). A similar result was obtained previously 3 , although in that case the two data types were integrated by first calling peaks individually and then combining the resulting P values using Fisher's combined probability test 3 . In our analysis, this two-step method was less successful than direct integrative analysis using DFilter (Fig.…”
Section: A N a Ly S I Smentioning
confidence: 58%
See 3 more Smart Citations
“…2d). A similar result was obtained previously 3 , although in that case the two data types were integrated by first calling peaks individually and then combining the resulting P values using Fisher's combined probability test 3 . In our analysis, this two-step method was less successful than direct integrative analysis using DFilter (Fig.…”
Section: A N a Ly S I Smentioning
confidence: 58%
“…The technology is now used to obtain genome-wide maps of histone modification, transcription factor binding, chromatin openness, gene expression, DNA methylation, replication origins and mRNA binding by microRNAs and ribosomes, to name but a few of the applications in a rapidly growing list [1][2][3] . At the same time, a plethora of bioinformatic tools has been developed for processing sequence-tag signals from the various assays.…”
Section: A N a Ly S I Smentioning
confidence: 99%
See 2 more Smart Citations
“…Another study also reported that rs405509 regulates APOE promoter activity (Artiga et al., 1998). Rs387976 ( NECTIN2 ), located in an open chromatin region, seems to mediate transcription factor binding (Song et al., 2011). Ten functional variants were found to exist in active expression states in multiple cell lines, ranging from 1 (rs387976) to 63 (rs157580 [ TOMM40 ]) of 68 cell types with data available from Ensembl.…”
Section: Resultsmentioning
confidence: 99%